Advanced Materials for Oral Application - Rusu, Laura-Cristina; Ardelean, Lavinia Cosmina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book consists of one editorial, 12 original research articles and two review papers from scientists across the world, with expertise in materials for dental application. The main subjects covered are: biomaterials and techniques for oral tissue engineering and regeneration; biomaterials for surgical reconstruction; CAD/CAM technologies and dedicated materials; novel restorative and endodontic materials and instruments.